Answer:
m=-3
x1,y1=1,-5
we have,
y-y1=m(x-x1)
y-(-5)=-3(x-1)
y+5=-3x+3
3x+y+2=0 is the required eqn
Answer: the first one
Step-by-step explanation:
It is the only one that is right
Answer:
a)= 2
b) 6.324
c) P= 0.1217
Step-by-step explanation:
a) The mean of the sampling distribution of X`1- X`2 denoted by ux`-x` = u1-u2 is equal to the difference between population means i.e = 2 ( given in the question)
b) The standard deviation of the sampling distribution of X`1- X`2 ( standard error of X`1- X`2) denoted by σ_X`1- X`2 is given by
σ_X`1- X`2 = √σ²/n1 +σ²/n2
Var ( X`1- X`2) = Var X`1 + Var X`2 = σ²/n1 +σ²/n2
so
σ_X`1- X`2 =√20 +20 = 6.324
if the populations are normal the sampling distribution X`1- X`2 , regardless of sample sizes , will be normal with mean u1-u2 and variance σ²/n1 +σ²/n2.
Where as Z is normally distributed with mean zero and unit variance.
If we take X`1- X`2= 0 and u1-u2= 2 and standard deviation of the sampling distribution = 6.324 then
Z= 0-2/ 6.342= -0.31625
P(-0.31625<z<0)= 0.1217
The probability would be 0.1217
Answer:
A
Step-by-step explanation:
The volume of a prism can be found by multiplying the area of the base by the height. It is the formula V = B*h. Here B = 108. Substitute and solve.
V = 108*8 = 864
This is answer A.
Answer:
6
Step-by-step explanation:
We can use ratios to solve
15 ft 18ft
---------- = -----------
5ft x
Using cross products
15x = 5*18
15x = 90
Divide by 15
15x/15 = 90/15
x =6